NextGenU.org's Free, Globally Available Online Training in Lifestyle Medicine. (March 2017) - Rossa-Roccor, Verena; Malatskey, Lilach; Frank, Erica
NextGenU.org now uniquely offers a free, accredited, globally-available online training in Lifestyle Medicine. Courses such as Lifestyle Medicine for Primary Care Physicians, Prevention and Treatment of Alcohol Use Disorders/Tobacco Use, Substance Use Disorder Screening, Public Health Nutrition, and more are competency-based and include knowledge transfer, a web-based global peer community of practice, and local, skills-based mentorships. Trainings use existing, expert-created resources from governments, universities, and medical specialty societies thus ensuring their quality and simultaneously making them free of costs, advertisement, and geographic barriers. To offer free credits for these courses, NextGenU.org partners with universities and professional societies.NextGenU.org 's comprehensive Lifestyle Medicine Curriculum will launch in early 2017.